Microbiome Structure of the Aphid Myzus persicae (Sulzer) Is Shaped by Different Solanaceae Plant Diets - He, Baoyu; Chen, Xiaoyulong; Yang, Hong; Cernava, Tomislav (Frontiers in Microbiology, 2021)
Myzus persicae (Sulzer) is an important insect pest in agriculture that has a very broad host range. Previous research has shown that the microbiota of insects has implications for their growth, development and environmental adaptation. So far, there is little detailed knowledge about the factors that influence and shape the microbiota of aphids. In the present study, we aimed to investigate diet-induced changes in the microbiome of M. persicae using high-throughput sequencing of bacterial 16S rRNA gene fragments in combination with molecular and microbiological experiments. The transfer of aphids to different plants from the Solanaceae family resulted in a substantial decrease in the abundance of the primary symbiont Buchnera. In parallel, a substantial increase in the abundance of Pseudomonas was observed; it accounted for up to 69.4% of the bacterial community in M. persicae guts and the attached bacteriocytes. In addition, we observed negative effects on aphid population dynamics when they were transferred to pepper plants (Capsicum annuum L.). The microbiome of this treatment group showed a significantly lower increase in the abundance of Pseudomonas when compared to the other Solanaceae plant diets, which might be related to the adaptability of the host to this diet. Molecular quantifications of bacterial genera that were substantially affected by the different diets were implemented as an additional verification of the microbiome-based observations. Complementary experiments with bacteria isolated from aphids that were fed with different plants indicated that nicotine-tolerant strains occur in Solanaceae-fed specimens, but they were not restricted to them. Overall, our mechanistic approach conducted under controlled conditions provided strong indications that the aphid microbiome shows responses to different plant diets. This knowledge could be used in the future to develop environmentally friendly methods for the control of insect pests in agriculture.